Traditional craftsmanship: the origin, culture and challenges of batik industry in Malaysia / Noor Haslina Mohamad Akhir … [et al.] - Mohamad Akhir, Noor Haslina; Ismail, Normaz Wana; Said, Rusmawati; Kaliappan, Shivee Ranjanee (Division of Research and Industry Linkages, UiTM Melaka, 2014)
Batik is a process of dyeing fabric by making use of a resist technique. Approximately, 70 percent of the national industry in Malaysia is derived from SMEs and microenterprises is one of the main components in SMEs. In the Malaysian context, most of batik enterprises have been categorized in SME industries. Recently, UNCTAD had classified the craft industry as one of the items in the creative industries. They believe the creative industries will provide new opportunities for developing countries to leapfrog into emerging high-income countries due to the contribution on output level, employment, and tourism sector. Even though batik production has a Jong-established in this country, unfortunately, it's still dominated by microenterprises with around 86 percent. Hence, this paper is written to bring readers to understand the origin, culture and the challenges faced by batik makers in order to preserve and flourish batik industry in Malaysia.